Inflammatory Fibroid Polyp Causing Ileo-ileal Intussusception in an Adult: A Rare Case Report - Mayur Suryavanshi; Milind Kesarkhane (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Inflammatory fibroid polyp (IFP) is a rare benign tumor-like lesion of the gastrointestinal tract, and it is an extremely rare cause of intussusception in adults. We present the case of a 58-year-old female who presented with abdominal pain and vomiting. The imaging findings showed ileo-ileal intussusception. The patient was operated on for the same. Histopathological examination revealed polyp with surface ulceration and composed of many thin-walled blood vessels along with plump fibroblast admixed with eosinophils, plasma cells, and lymphocytes. This case is presented for its rare cause of intussusception in adults and hence to emphasize the role of histology.